2012
DOI: 10.4315/0362-028x.jfp-11-467
|View full text |Cite
|
Sign up to set email alerts
|

Depuration of Oysters (Crassostrea gigas) Contaminated with Vibrio parahaemolyticus and Vibrio vulnificus with UV Light and Chlorinated Seawater

Abstract: The efficacy of depuration using UV light and chlorinated seawater for decontaminating Vibrio parahaemolyticus and Vibrio vulnificus from oysters was investigated. Oysters were contaminated with a five-strain cocktail of V. parahaemolyticus or V. vulnificus to levels of 10(4) to 10(5) CFU ml(-1) for bioaccumulation. The depuration was conducted in a closed system in which 350 liters of seawater was recirculated at a rate of 7 liters/min for 48 h at room temperature. Counts of V. parahaemolyticus or V. vulnif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…were still detectable, albeit at low concentrations. Barile et al (2009), Wang et al (2010, Ramos et al (2012), and Su et al (2010) observed the same trends for Vibrio parahaemolyticus. These bacteria remained in oysters for up to 2 wk.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…were still detectable, albeit at low concentrations. Barile et al (2009), Wang et al (2010, Ramos et al (2012), and Su et al (2010) observed the same trends for Vibrio parahaemolyticus. These bacteria remained in oysters for up to 2 wk.…”
Section: Discussionsupporting
confidence: 66%
“…However, procedures combining depuration with other postharvest decontamination methods, such as applying high hydrostatic pressure or irradiation, are suitable (Jakabi et al 2003, Depaola et al 2009, Ramos et al 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies focused on testing depuration in different types of water (Vasconcelos & Lee 1972, Kasai et al 2011, Ramos et al 2012, and at different temperatures (Chae et al 2009, Love et al 2010, Lopez-Joven et al (Rowse & Fleet 1984, Power & Collins 1990, Love et al 2010, and densities (Lee 2010). However, there is little information on tropical oysters (Pillai & Selvan 1987) and no information on the effect of high-density stocking on depuration of tropical bivalves.…”
Section: Introductionmentioning
confidence: 99%
“…Even though exogenous bacteria usually rapidly depurate around 72 to 96 h after introduction, the endogenous bacteria are notoriously resistant to depuration and using this technique has not been shown to increase the uptake of laboratory-grown bacteria (9,11,23,28,30). Allowing the oysters to bathe in high (Ͼ30‰)-salinity water before experimentation has proven successful in reducing the resident bacterial levels before beginning bioaccumulation experiments (8,17). Further information on the effects of water with elevated salinity on oyster V. vulnificus populations is presented below.…”
mentioning
confidence: 99%
“…The "core" method is described first, followed by examples of deviation from this formula. The core method, elegant in its simplicity, is to grow the bacterial strain of interest to the desired concentration and seed an aquarium with a specific concentration of those bacteria, while allowing oysters within that aquarium to bioaccumulate the cells (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). The use of this method often yields similar results in which the bacteria are rapidly and significantly taken up by the oysters but quickly depurated to minimal or nondetectable levels within a few days (11,12,19,(22)(23)(24).…”
mentioning
confidence: 99%